The Diffusion of Mexican Immigrants During the 1990s: Explanations and Impacts - David Card; Ethan Lewis (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2005)
Mexican immigrants were historically clustered in a few cities, mainly in California and Texas. During the past 15 years, however, arrivals from Mexico established sizeable immigrant communities in many "new" cities. We explore the causes and consequences of the widening geographic diffusion of Mexican immigrants. A combination of demand-pull and supply push factors explains most of the inter-city variation in inflows of Mexican immigrants over the 1990s, and also illuminates the most important trend in the destination choices of new Mexican immigrants - the move away from Los Angeles. Mexican inflows raise the relative supply of low-education labor in a city, leading to the question of how cities adapt to these shifts. One mechanism, suggested by the Hecksher Olin model, is shifting industry composition. We find limited evidence of this mechanism: most of the increases in the relative supply of loweducation labor are absorbed by changes in skill intensity within narrowly defined industries. Such adjustments could be readily explained if Mexican immigrant inflows had large effects on the relative wage structures of different cities. As has been found in previous studies of the local impacts of immigration, however, our analysis suggests that relative wage adjustments are small.
Keywords: 330